The Good Samaritan Parable Revisited: A Survey During the COVID-19 Pandemic - Lu, Yong (Frontiers in Psychology, 2022)
From an integrative approach of parable interpretation that combines ethical, evolutionary, historical, and psychological perspectives, the current research empirically examined the purely theorized argument for interpreting the actions of the priest, Levite, and Samaritan in the good Samaritan parable (Lk. 10:25-37) by the regulatory focus theory (Lu, 2017b). In one experiment conducted during the COVID-19 outbreak, 93 Polish participants were randomly assigned to a simulated vignette of the good Samaritan parable where either the prevention or promotion regulatory focus was manipulated. The results confirmed a certain favorable tendency to offer quasi-realistic help in both the regulatory focus conditions. The finding highlights a dynamic association in goal pursuit motivation and prosocial behavior in a pandemic context regarding the good Samaritan parable.